P385 Analysis of EEG correlates during n-back working memory test in epilepsy patients investigated with surface and invasive electrodes. Issue 9 (September 2017) - Bajzat, Bettina; Halasz, Peter; Eross, Lorand; Fabo, Daniel
Abstract : Introduction: The brain process of short term storage of multimodal information is called generally as working memory. This is thought to be located in the frontal and parietal lobes, however recent evidences show that the temporal lobe has important function in maintaining short-term and spatial information. Among multiple neuropsychological tests used for short term memory, the N-back test (NBT) has the advantage, that higher values of memory load can be set by increasing the recall distance (value n ). Methods: We involved therapy resistant epilepsy patients undergoing video-EEG with scalp and invasive intracranial electrodes for visual and verbal NBT. The stimuli were presented gradually from 0 to 2 backs. The EEG graphs were filtered and averaged, and time-frequency analysis was performed (EEGLAB). Results: Verbal NBT showed significant left-sided increase in gamma power, while during visual NBT right-sided gamma power increase was observed. The power correlated with the elevation of memory load. Intracranial data showed less increase in frontal regions compared to temporal. Conclusions: Increase of gamma power seemed to be a good psychoneural correlate of memory processes during verbal and visual NBT. It showed appropriate lateralization and correlation with memory load. Based on our preliminary data the role of temporal lobe in short term memory can be hypothesized. We plan to include more patients.